Teaching Grammar and Developing It with a Worksheet Based on The Cognitive Approach to Improving Students’ Grammar Ability: تعليم القواعد و تطويره بورقة العمل على أساس المدخل المعرفي لترقية قدرة الطلاب على القواعد - Azwir, Azwir; Basa, Ali; Mukhlisah, Mukhlisah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
Based on the challenges students encounter in understanding grammatical and morphological materials, this research aims to enhance the teaching of grammatical rules by using worksheets based on the cognitive approach. This is due to the students' difficulties in grasping the grammatical rules they have learned. The worksheets were developed specifically to address this need. The students' learning conditions were consistently focused on comprehending grammar materials. The research utilized direct observation, questionnaires, expert validation, and testing as tools, and the results obtained indicate that teaching grammar using a worksheet based on the cognitive approach effectively improves students' ability to understand and apply grammatical rules.